2005
DOI: 10.1159/000088906
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro Study of Affected Dentin as a Risk Factor for the Development of Secondary Caries

Abstract: The objective of the study was to investigate the association between the presence of residual caries (inner affected dentin) on the cavity walls of cavity preparations and the further development of secondary caries lesions. Two 2 × 5 × 2 mm cavities, one in the apical portion (A) and one in the cervical portion (C) of the root, were prepared on both the lingual (L) and buccal (B) surfaces of 18 extracted human roots. The apical cavities (AB and AL) were artificially demineralized for 30 min using a decalcify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…They often utilized conventional methods of cavity preparation and restorations before incubating tooth specimens with chemical solutions or bacterial cultures [Kidd, 1976;Gilmour et al, 1990;Donly and Gomez, 1994;Sepet et al, 1995;Dionysopoulos et al, 1996;Fontana et al, 1996a;Matharu et al, 2001;Lobo et al, 2005;Seemann et al, 2005;Borczyk et al, 2006]. The in vitro model developed for this study provided further standardization of the gap size and specimens (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…They often utilized conventional methods of cavity preparation and restorations before incubating tooth specimens with chemical solutions or bacterial cultures [Kidd, 1976;Gilmour et al, 1990;Donly and Gomez, 1994;Sepet et al, 1995;Dionysopoulos et al, 1996;Fontana et al, 1996a;Matharu et al, 2001;Lobo et al, 2005;Seemann et al, 2005;Borczyk et al, 2006]. The in vitro model developed for this study provided further standardization of the gap size and specimens (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Ricketts et al suggest that there is insufficient evidence to know whether it is necessary to re‐enter after a period of time and excavate further, but studies that have not re‐entered do not report adverse consequences. It has also been shown that the presence of affected dentine did not increase the susceptibility to secondary caries 70 …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Bjorndal 25 indicated that if an excellent marginal adaptation is maintained, the presence of little remaining caries in the depth of the cavity may not cause a problem for short-term success of the restoration. Borczyk et al 26 reported that the presence of affected dentin did not predispose tooth tissue to secondary caries formation. Although, complete removal of all decayed dentin had been advocated in the past during cavity preparation, a more conservative approach is to remove any demineralization in the external cavity walls (mesial, distal, gingival, buccal and lingual) during excavation, but leave softened affected dentin in pulpal and axial surfaces in order to prevent pulpal exposure.…”
Section: Discussionmentioning
confidence: 99%